Metode Pembelajaran Bahasa Arab: antara Tradisional dan Modern - Sapri Sapri (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
: Teaching method is one of educational elements. The exist of a good method in the teaching learning process is to be because it can help to get hope goal of an instructional. In Arabic instructional, a teacher must use various method throught it is conventional or modern.Â